The digital flood : diffusion of information technology across the U.S., Europe, and Asia - Cortada, James W. (New York ; Oxford : Oxford University Press, 2012)
The history of how computers spread to over 20 nations globally in less than six decades, exploring economic, political, social and technological reasons and consequences. It is based on extensive research into primary and secondary sources, and concludes with a discussion of implications for key players in the globalized economy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Electronic digital computers -- History; Electronic digital computers -- Social aspects; Technology transfer